The art of intelligence simulations, exercises, and games - Arcos, Ruben; Lahneman, William J. (Security and professional intelligence education series (SPIED), 2014)
This book offers original simulations, exercises, and games designed by academics and intelligence professionals from several countries. These innovative methods are meant to enhance the learning experience and provide an international perspective to the topics and approaches discussed in class. Intelligence simulations and games are presented in ready-to run formats, from easy instructions to result recordings matrices, to minimize preparation time for both instructors and students.